Phenotypes of chronic inflammatory demyelinating polyneuropathies with manifestation after coronavirus infection COVID-19 - Yana B. Kushnir; Alexander I. Bezvodinskikh; Anastasia V. Vladykina; Natalia A. Totolyan (LLC "MEDIAFORMAT", 2024)
Chronic inflammatory demyelinating polyneuropathy (CIDP) is an orphan disease of the peripheral nervous system. The clinical phenotypes of CIDP may influence the choice of primary pathogenetic therapy. In some cases, viral infection may be a trigger for the development of an immune-mediated process. The role of coronavirus infection (COVID-19) as a trigger of the clinical manifestation of CIDP, as well as the impact of COVID-19 on the disease course and response to pathogenetic therapy remains an unexplored issue. The paper presents a series of clinical cases CIDP with manifestations after COVID-19 infection and review of publications.